PHYSICAL DEVELOPMENT OF CHILDREN WITH PATHOLOGY OF TONSILS AND ADENOIDS - Татьяна Александровна Нагаева; Дарья Алексеевна Пономарева; Елена Александровна Фурманова; Виктор Александрович Желев; Евгений Викторович Михалев (The Publishing House Medicine and Enlightenment, 2016)
There was conducted a study of the physical development of 85 4-6 year old preschool children with pathology of the tonsils and adenoids. Chronic diseases of adenotonsillar system (chronic tonsillitis, chronic adenoids) were observed in 40 children, functional pathology (adenoid hypertrophy, hypertrophy of the tonsils) - 45 children. Analysis of the parameters of physical development of the examined preschool children showed that 39,2 % of preschool children with diseases of the tonsils and adenoids manifest developmental disabilities, the severity of which depends on the nature of the pathology. Children with chronic diseases of tonsils and adenoids significantly more often have low values of height and weight. Children with functional disorders of adenotonsillar system oftener have high growth parameters, at the same time deviations of mass index of multidirectional nature are equally represented with deficiency (35,6 %) and abundant (37,8 %) of body weight. There was determined disharmonious physical development among majority of pre-school children (70 %) with the pathology of the tonsils and adenoids. The survey results demonstrate the need for a differentiated approach to the assessment of physical development in children with tonsils and adenoids pathology depending on the form of defeat of epipharynx.